Masalah Batas-batas Bangsa - Usman Pelly (Antropologi Indonesia, 1997)
In the first part of this article, the author presents theories about the concept of nation which has been developed since the early 20th century. By presenting these theories the author aims to reveal the ambiguities of the concept of nation that has been developed by various scholars. The explanation focuses only on certain group in the society, whereas the subject contains psychological and emotional values which are difficult to be examined objectively. Another problem is the construction of the concept of nation based on more than one discourse. The author describes further the explanation of the concept of nation from the anthropological viewpoints. Malinowski relates the concept of nation to the existence of ethnic groups. Leach and Barth revise Malinowski's concept in their discussion about ethnic boundaries. Within the political and historical discourses, the concept of nation relates to the objective and subjective relations with the state as developed by Mill and Renan. In the post Second World War, the concept of nation is associated with the emergence of nation-states, the presence of social awareness of colonialism and set upon many ethnic groups as stated by Anderson. At the end, the author depicts the problem faced by the Indonesian in their efforts to maintain the existence of their nation-state and provides alternatives to solve the problem.